2011
DOI: 10.1186/1756-3305-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Larval migration in PERL chambers as an in vitro model for percutaneous infection stimulates feeding in the canine hookworm Ancylostoma caninum

Abstract: BackgroundAncylostoma caninum third-stage larvae are the non-feeding infective stage of this parasite and are able to infect potential hosts via different infection routes. Since percutaneous infection is one of the most important routes and skin penetration is the first step into parasitic life, an existing in vitro model for percutaneous migration was modified and evaluated. The main parameter used to evaluate migration was the migration ratio (migrated larvae as a percentage of total number of larvae recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…Excised native skin and simple hydrogels were generally used so far to study the penetration behavior of skin-invading parasitic helminths (Franke et al, 2011;Haas, 2003;McKerrow and Salter, 2002;Safer et al, 2007). Already 1993, Fusco et al (1993 studied the penetration success of S. mansoni into human skin equivalents derived from fibroblast and keratinocyte layers embedded in a collagen scaffold.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Excised native skin and simple hydrogels were generally used so far to study the penetration behavior of skin-invading parasitic helminths (Franke et al, 2011;Haas, 2003;McKerrow and Salter, 2002;Safer et al, 2007). Already 1993, Fusco et al (1993 studied the penetration success of S. mansoni into human skin equivalents derived from fibroblast and keratinocyte layers embedded in a collagen scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…The infection of human full skin was performed in Franz type diffusion chambers (Gauer Glas, Puettlingen, Germany). This chamber system allows the application of a tissue with a higher thickness, compared to the skin equivalents (Franke et al, 2011). Human skin and ex vivo epidermis were prepared one day before the infection experiments.…”
Section: Preparation Of Human Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies deploying in vitro models of skin penetration by iL3 of Strongyloides spp. and hookworms such as Ancylostoma spp., which may also invade the host percutaneously, have revealed that this event may trigger early events comprising reactivation of these developmentally quiescent infective larvae [72,73]. These model systems generally involve a glass apparatus, dubbed a PERL chamber that comprises upper and lower compartments filled with a physiological medium, the lower compartment being warmed to host body temperature, and separated by a layer of mammalian skin recovered from some laboratory animal at necropsy.…”
Section: Animal and In Vitro Models For The Study Of Human Strongyloimentioning
confidence: 99%